2015
DOI: 10.1136/bjophthalmol-2015-306987
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of as needed versus treat and extend ranibizumab or bevacizumab treatment regimens for neovascular age-related macular degeneration

Abstract: Though our study suggests superiority of the treat and extend regimen to PRN treatment in a 12-month period, this review demonstrates the need for randomised clinical trials to confirm our findings and to evaluate long-term efficacy outcomes with these regimens compared with monthly therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
86
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 11 publications
3
86
0
4
Order By: Relevance
“…[15][16][17]19 Furthermore, recent investigations have documented that for a better response repeated injections are needed, at least initially, irrespective of the response to therapy. 13,[20][21][22] However, very little is known about the dosing and the possible local side effects in the retina of repeated IVI. 23 Indeed, bevacizumab and ranibizumab are humanized monoclonal antibodies and thus may trigger even in humans an inflammatory reaction, as has been shown for higher doses of these substances, 24 and the trap aflibercept may even be more inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]19 Furthermore, recent investigations have documented that for a better response repeated injections are needed, at least initially, irrespective of the response to therapy. 13,[20][21][22] However, very little is known about the dosing and the possible local side effects in the retina of repeated IVI. 23 Indeed, bevacizumab and ranibizumab are humanized monoclonal antibodies and thus may trigger even in humans an inflammatory reaction, as has been shown for higher doses of these substances, 24 and the trap aflibercept may even be more inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Several pro re nata regimens have been evaluated as alternatives to fixed dosing regimens [5][6][7] . However, pro re nata treatment has been found to be generally inferior over the long term, a result not surprising given that treatments are only administered once retinal exudation has recurred [8] .…”
mentioning
confidence: 99%
“…27 Their systematic review demonstrated a gain of 9.17 (S.D. 3.8) ETDRS letters as a weighted mean at one year, with 8.34 (S.D.…”
Section: Discussionmentioning
confidence: 99%